An injection‐locked green InGaN diode laser. Issue 5 (23rd November 2021) - Chen, Xiaoming; Xu, Ying; Tsai, Chin‐Chun; Chen, Yi‐Hsi; Chen, Nan‐Kuang; Chui, Hsiang‐Chen
Abstract: We designed a single‐frequency green laser system that can deliver a 60‐mW frequency‐tunable single‐longitudinal‐mode laser beam, having a 6.5 MHz linewidth at around 519 nm. An external cavity diode laser can provide a wavelength‐tunable single frequency laser beam, but its output power is limited. Therefore, an injection‐locked laser was designed with a Fabry–Perot type green InGaN laser diode in an external Littrow‐type cavity as the master laser and another laser diode of the same model as the slave laser. Injection locking can effectively enhance the output power and narrow the linewidth of the master laser. We found that the injection locking occurred at longitudinal mode matching between the master laser and slave laser diodes, which is located at a specific frequency for a periodical applied current. The side peaks of the injection locking due to the transverse mode mismatching were recorded and analyzed.